NodeMCU ESP32 Motorcycle Electrical Monitoring System: Sistem Pemantauan Kelistrikan Sepeda Motor NodeMCU ESP32 - Dony Hari Ramadhan; Dr. Syamsudduha Syahrorini ST., MT (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Motorcycle electrical systems are essential for supporting engine operation and vehicle functionality, yet electrical faults often require time-consuming manual inspection. Specific Background: Conventional troubleshooting commonly involves dismantling motorcycle body parts and measuring electrical components using instruments such as avometers, making the process impractical for riders and workshop personnel. Knowledge Gap: Existing monitoring studies have addressed electrical parameter observation in other applications, but a system specifically designed to monitor motorcycle electrical components and provide real-time fault notifications through a smartphone remained limited. Aims: This study aimed to develop a NodeMCU ESP32-based motorcycle electrical monitoring system capable of monitoring battery, headlight, horn, and starter electrical conditions and delivering notifications via Telegram. Results: The developed system operated optimally by monitoring voltage values through DC voltage sensors and transmitting data to a smartphone application. The displayed voltage readings were clear and accurate, with normal electrical conditions showing corresponding voltage values and damaged components displaying a value of 0. The system achieved a data transmission delay of 1.14 seconds, while the average difference in delivery delay remained relatively small at 0.4%. Novelty: The study presents a motorcycle electrical monitoring system integrating DC voltage sensors, NodeMCU ESP32, and Telegram-based notifications for real-time detection of electrical faults in key motorcycle components. Implications: The system enables riders to identify electrical faults more quickly without manual inspection procedures and provides accessible information regarding motorcycle electrical conditions through a smartphone-based platform.Highlights: Smartphone alerts provided immediate identification of battery, headlight, horn, and starter faults. Voltage readings corresponded to component status, with damaged circuits indicated by zero-value measurements. Data delivery through Telegram was achieved with a transmission delay of 1.14 seconds and a small average delay difference. Keywords: NodeMCU ESP32; Motorcycle Electrical System; DC Voltage Sensor; Real-Time Monitoring; Telegram Notification